Impact of digital literacy and interpersonal communication on prospective teacher readiness of automotive engineering education - Utami, Nunik Widia; Iskandar, Ranu; Naryanto, Rizqi Fitri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Digital literacy equips prospective teachers with essential information and communication technology (ICT) skills, while interpersonal communication enables them to interact effectively with students and the community. However, the impact of these skills on the readiness of prospective teachers, especially in the Automotive Engineering Education Study Program, has not been widely studied. This study attempts to examine how digital literacy influences students' readiness to become teachers in this study program. A quantitative approach was used in this study, the data collection process used the help of an online questionnaire with a population of 2019 and 2020 PTO students with a sample determined by the Slovin method of 62 students. The results showed an R2 value of 0.389, which means 38.9% of the variance in teacher readiness can be explained by digital literacy. In addition, a positive correlation (R = 0.623) is shown in the relationship between variables. Meanwhile, the coefficient B of digital literacy is 0.373. This indicates that as the digital literacy and interpersonal communication skills of PTO students of Semarang State University increase, their readiness to become teachers also increases. The conclusion from this study is that digital literacy and interpersonal communication have a significant effect on the readiness of prospective teachers of PTO students of Semarang State University.